Active Learning to Find Concepts and Algorithms in Decimal Material in Class V Elementary School - Taruly Tampubolon; Robert Harianja; Sariayu Sibarani (International Journal of Social Service and Research (IJSSR), 2023)
Prior to learning, pre-tests and questionnaires were given to determine students' abilities and interests in learning decimal. Based on the results of the initial test, it was found that students' initial abilities were very low with an average grade of 15.50, and from the results of the questionnaire, all students said they did not like decimal learning. After active learning to find the concept of algorithms in decimal material, the class average value was 86.27, meaning that the level of classical student mastery was 86.27. This indicated that the student mastery level was relatively high. Of the 20 students, there were 19 people or 95.0% who had finished studying, thus that classically learning decimal material had been completed. Judging from the specific learning objectives, all of them achieved above 65%. The results of the student questionnaire after the decimal material learning outcomes test was completed, obtained data that students felt happy with the learning they had just participated in. Students argue, the way is easy to understand and understand. With simple but interesting teaching aids, it can increase students' enthusiasm and interest in learning Mathematics. The classical learning outcomes have been completed based on the learning completeness criteria specified in the curriculum, specific learning objectives have been achieved based on the learning objectives achievement criteria, the student's response to learning is positive, the student's mastery of the material is high. It can be concluded that learning on decimal material in class V SD. already effective.